KEJADIAN LUAR BIASA ANTRAKS DI KABUPATEN BOYOLALI 2011 - Farrah Fahdhienie; Desi Ari Apsari; Anggun Paramita Djati (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2012)
Anthrax is a zoonotic disease that can attack various types of livestock and humans and cause death in high numbers. Boyolali is one of anthrax infected areas since 1990. On Saturday February 12, 2011, the Public Health received a report from the health center Boyolali Klego II regarding alleged cases of anthrax outbreaks in Hamlet Village defense Karangmojo Klego Boyolali District. The purpose of this activity to find out and get an idea of skin anthrax outbreak in the Village District Karangmojo Klego Boyolali.Materials and Methods: Diagnosis based on clinical symptoms and the investigation is descriptive to 16 people with anthrax.Results and Discussion: The case has a fever (100%), flushing fluid swelling (100%), necrotic tissue in the wound (100%), black crust covered the wound (81.3%), swelling of the skin (81.3% ). Conclusions and Recommendations: skin anthrax outbreak occurred in the Hamlet defense in 16 residents. It is suggested that this outbreak does not happen again is to enable surveillance of anthrax in the health office Boyolali, increasing public knowledge and vaccination of livestock on a regular basis.